Migratory patterns and seasonal habitat use of great hammerhead sharks ( Sphyrna mokarran ) in the southeastern United States - Grace A. Casselberry; Gregory B. Skomal; Lucas P. Griffin; Jacob W. Brownscombe; John T. Finn; Joseph Dello Russo; Alex Filous; Peter E. Holder; Ben Daughtry; Jeff Kneebone; Danielle Morley; Susan K. Lowerre‐Barbieri; et al. (Journal of Fish Biology, 2025)
The great hammerhead shark ( Sphyrna mokarran ) is a highly mobile shark species whose population in the United States declined dramatically through the early 2000s. Their spatial ecology is poorly understood, creating challenges for effective conservation of this enigmatic marine predator. Using acoustic telemetry and network analyses, we describe the movement patterns of 15 mature great hammerhead sharks (207–331.5 cm fork length) primarily within the waters of the southeastern United States from April 2019 to December 2022, including identifying movement corridors, core use areas and seasonal shifts in habitat use. Great hammerheads exhibited partial migration; some sharks undertook consistent, repeatable, round‐trip migrations between the tagging site in the Florida Keys and northern points in the Gulf of Mexico and Atlantic coast. Conversely, others remained in the Florida Keys year‐round. Network analysis coupled with community detection algorithms revealed that individual great hammerheads displayed oceanic basin affinity, favouring migration to either the Atlantic Ocean or Gulf of Mexico. Great hammerheads that remained in the Florida Keys shifted their habitat use seasonally from inshore channels (spring and summer) to offshore artificial reefs and the natural reef tract (summer through winter). These shifts may be driven by prey availability, as core use areas often corresponded to known locations of seasonal spawning aggregations for reef fish. These data fill an important knowledge gap for great hammerhead migratory patterns that can improve spatial management strategies for this historically overexploited species. We discuss the importance of drawing upon data from multiple tagging locations for highly mobile species management, particularly in the designation of essential fish habitat.

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

Individual variation and repeatability of Atlantic tarpon Megalops atlanticus migrations in the southern US: implications for conservation and management - Lucas P. Griffin; Jacob W. Brownscombe; Aaron J. Adams; JoEllen K. Wilson; Grace A. Casselberry; Peter E. Holder; Alex Filous; Susan K. Lowerre-Barbieri; Steven J. Cooke; Andy J. Danylchuk (Marine Biology, 2023)

Correction to: Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Bonefishes in Hawai’i and the importance of angler-based data to inform fisheries management - Keith T. Kamikawa; Alan M. Friedlander; Kimberlee K. Harding; Alex Filous; Mary K. Donovan; Eva Schemmel (Environmental Biology of Fishes, 2015)